The Depression Prevention Initiative: Trauma as a Moderator of Prevention Outcomes. (December 2022) - Sbrilli, Marissa D.; Jones, Jason D.; Kanine, Rebecca M.; Gallop, Robert; Young, Jami F.
Interpersonal Psychotherapy-Adolescent Skills Training (IPT-AST) is an evidence-based indicated depression prevention program that has been shown to reduce depression symptoms. Research is needed to identify moderators of IPT-AST's effects. Although trauma history has emerged as a moderator of depression treatment outcomes, the impact of trauma on short- and long-term outcomes in the context of preventive interventions for adolescent depression is unknown. This study examines the impact of trauma on prevention outcomes in a school-based randomized controlled trial (RCT) in which 186 adolescents (mean age = 14.01 years, SD = 1.22; 67% female) were randomly assigned to IPT-AST delivered by research staff or to group counseling (GC) provided by school counselors. Trauma history significantly moderated intervention outcomes during the active phase of the intervention but not during long-term follow-up. During the active phase, youth in IPT-AST with low or no trauma exposure experienced significantly greater reductions in depression symptoms than youth in GC with low or no trauma exposure, but there were no significant differences in rates of change between the two interventions for youth with high or any trauma exposure. These findings highlight the importance of assessing trauma and investigating whether these interventions can be tailored or supplemented to enhance the effects for youth with trauma exposure.